2010
DOI: 10.1002/lapl.200910151
|View full text |Cite
|
Sign up to set email alerts
|

1064 nm Nd:YAG laser intracavity pumped at 946 nm and sum-frequency mixing for an emission at 501 nm

Abstract: We present for the first time a Nd:YAG laser emitting at 1064 nm intracavity pumped by a 946 nm diode-pumped Nd:YAG laser. A 809 nm laser diode is used to pump the first Nd:YAG crystal emitting at 946 nm, and the second Nd:YAG laser emitting at 1064 nm intracavity pumped at 946 nm. Intracavity sum-frequency mixing at 946 and 1064 nm was then realized in a LBO crystal to reach the cyan range. We obtained a continuous-wave output power of 485 mW at 501 nm with a pump laser diode emitting 25.4 W at 809 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…At the same time, using a laser beam analyser (ModeScan Model 1780), wavelength outputs at 1064, 532, and 355 nm laser was obtained with a respective X axis factor of 5.83, 4.25, and 6.32, and Y axis factor of 5.61, 4.08, and 6.15. This is due to rela tive to the intracavity frequency changes process of multiple entries [23][24][25][26], extracavity one way nonlin ear frequency change process is not conducive to the Output power of 335 nm UV laser, mW improvement of the laser mode, resulting in relatively poor quality of the SHG laser beam and SFG laser beam.…”
Section: Sfg (Sum Frequency Generation) Experimentsmentioning
confidence: 99%
“…At the same time, using a laser beam analyser (ModeScan Model 1780), wavelength outputs at 1064, 532, and 355 nm laser was obtained with a respective X axis factor of 5.83, 4.25, and 6.32, and Y axis factor of 5.61, 4.08, and 6.15. This is due to rela tive to the intracavity frequency changes process of multiple entries [23][24][25][26], extracavity one way nonlin ear frequency change process is not conducive to the Output power of 335 nm UV laser, mW improvement of the laser mode, resulting in relatively poor quality of the SHG laser beam and SFG laser beam.…”
Section: Sfg (Sum Frequency Generation) Experimentsmentioning
confidence: 99%
“…Successful attempts to lase the Nd:LuVO 4 have been reported [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Recently, the Nd:LuVO 4 laser under direct 880 nm diode laser pumping was reported [53][54][55][56][57][58]. In 2010, Lü et al reported diode pumped Nd:LuVO 4 laser emitting at 1089 nm for the first time.…”
Section: Introductionmentioning
confidence: 98%
“…In 2010, Y.F. Lü reported for the first time a Nd:YAG laser emitting at 1064 nm intracavity pumped by a 946 nm diode pumped Nd:YAG laser.They obtained a contin uous wave output power of 485 mW at 501 nm with a pump laser diode emitting 25.4 W at 809 nm [14]. However, all above the sum frequency laser worked in multimode, which limited the extensive application range of it.…”
Section: Introductionmentioning
confidence: 99%